Pengaruh Kompetensi Sosial Guru Terhadap Peningkatan Sikap Sosial Para Siswa di SDN Tanah Merah - Angkut Ana Sari; Ana pertiwi; Khasbi Ainun Najib (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
Social competence is the ability of teachers to communicate and interact with students during the learning process. This competence is very important so that teachers can be good examples for students, help students develop individuals who are full of empathy, attention, and concern for others. This study aims to assess in detail the influence of social competence possessed by classroom teachers. This study uses a qualitative approach. The main subjects of the study, namely teachers and supporting objects, namely students. Data collection techniques through observation, interviews, and documentation. Data were analyzed using Miles and Huberman's theory, including data reduction, data presentation, and drawing conclusions. The results of the study showed that teacher social competence, including inclusive attitudes, polite communication, adaptability, and communication with the professional community, had a positive effect on the learning process. Teachers who are effective in social competence create a pleasant learning atmosphere, increase comfort, motivation, and student learning achievement. This study concludes the importance of strengthening social competence in improving the quality of the learning process in the classroom.